Introducing Architecture to Early Childhood through Play-Based Community Service at a Bandar Lampung Kindergarten - Novita Hillary Christy Damanik; Guruh Kristiadi Kurniawan; Nova Asriana; Stirena Rossy Tamariska; Galuh Fajarwati (LKP KARYA PRIMA KURSUS, 2026)
Early childhood education in Indonesia remains oriented toward basic literacy and numeracy, while learning about space, form, and the built environment is rarely introduced, even though spatial ability develops rapidly and is highly malleable at a young age. This community service program addressed that gap by introducing basic architectural concepts to kindergarten children through a one-day, play-based workshop at TK Negeri 2 Bandar Lampung. Involving five lecturers and twelve architecture students, the program used visual media, drawing, shape puzzles, cardboard model-making, and an environmental “little architect” role-play, with achievement assessed through a three-indicator facilitator observation rubric (conceptual understanding, creativity, and engagement). Facilitator observation indicated a marked increase in children’s recognition of basic building shapes and functions and in their enthusiasm for design-relateed play, suggesting that early, playful exposure to architectural thinking is feasible and worth institutionalizing in kindergarten curricula.